Analysis of the ACTN3 gene in high performance sports practice: a narrative review - Camilo, Danieli Amorim (2021)
Objective: To analyze the ACTN3 gene in high performance sports, as well as to verify the relationship with performance in the specific sport and the influence of the ACTN-3 gene on the characterization of muscle fibers. Methodology: This is a study of narrative literature review, which analyzed articles published in Portuguese and/or English, between 1995 and 2020, found on the Google Academic search platform, selected from the keywords, synonyms and descriptors “genetic”, “polymorphism”, “performance” and “actn3”. Full-text studies available online, free of charge, were included, providing information on human genetics, the ACTN3 gene polymorphism, the influence of genetics on sports performance and the types of muscle fibers and their intervention in sport, totaling 41 articles . Results: The analysis resulted in a categorization, separated by five themes that should be considered within the prescription and practice of high performance sports: a) Biological individuality: genetics in sport; b) Actin; c) Genetic polymorphism; d) ACTN3 RR, XX, RX genotype; e) The R577X polymorphism of the ACTN3 gene: relationship between genetics and muscle fiber type. Final Considerations: The expression of the ACTN3 gene favors the sports performance of athletes who exercise strength/speed. People with the mutant genotype perform better when it comes to aerobic endurance sports. Thus, in addition to the intrinsic factors, the extrinsic factors need to be constantly manipulated, such as adequate training, rest and feeding routine, which are essential for a good performance.